Nanosculpt: A methodology for generating complex realistic configurations for atomistic simulations - Prakash, Aruna; Hummel, Martin; Schmauder, Siegfried; Bitzek, Erik (MethodsX, 2016)
Atomistic simulations have now become commonplace in the study of the deformation and failure of materials. Increase in computing power in recent years has made large-scale simulations with billions, or even trillions, of atoms a possibility. Most simulations to-date, however, are still performed with quasi-2D geometries or rather simplistic 3D setups. Although controlled studies on such well-defined structures are often required to obtain quantitative information from atomistic simulations, for qualitative studies focusing on e.g. the identification of mechanisms, researchers would greatly benefit from a methodology that helps realize more realistic configurations. The ideal scenario would be a one-on-one reconstruction of experimentally observed structures. To this end, we propose a new method and software tool called nanosculpt with the following features:The method allows for easy sample generation for atomistic simulations from any arbitrarily shaped 3D enclosed volume.The tool can be used to build atomistic samples from artificial geometries, including CAD geometries and structures obtained from simulation methods other than atomistic simulations.The tool enables the generation of experimentally informed atomistic samples, by e.g. digitization of micrographs or usage of tomography dat
Keywords: 3D materials science; Atom probe tomography; Digitized microstructure; Experimentally informed atomistic simulations; Molecular dynamics simulations; Ni-base superalloy